2010
DOI: 10.1186/1471-2377-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Program of rehabilitative exercise and education to avert vascular events after non-disabling stroke or transient ischemic attack (PREVENT Trial): a multi-centred, randomised controlled trial

Abstract: BackgroundDespite lack of outward signs, most individuals after non-disabling stroke (NDS) and transient ischemic attack (TIA) have significant cardiovascular and cerebrovascular disease and are at high risk of a major stroke, hospitalization for other vascular events, or death. Most have multiple modifiable risk factors (e.g., hypertension, physical inactivity, hyperlipidaemia, diabetes, tobacco consumption, psychological stress). In addition, accelerated rates of depression, cognitive decline, and poor quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 80 publications
0
18
0
1
Order By: Relevance
“…210,211 Several studies have shown that aerobic exercise and strength training will improve cardiovascular fitness after stroke. 197,[210][211][212][213][214][215] Structured programs of therapeutic exercise have been shown to improve mobility, balance, and endurance, 213 and beneficial effects have been demonstrated in different ethnic groups and in both older and younger patients. 216 Together, these studies provide important information on the safety and selected clinical benefits of exercise after stroke.…”
Section: Strokementioning
confidence: 99%
“…210,211 Several studies have shown that aerobic exercise and strength training will improve cardiovascular fitness after stroke. 197,[210][211][212][213][214][215] Structured programs of therapeutic exercise have been shown to improve mobility, balance, and endurance, 213 and beneficial effects have been demonstrated in different ethnic groups and in both older and younger patients. 216 Together, these studies provide important information on the safety and selected clinical benefits of exercise after stroke.…”
Section: Strokementioning
confidence: 99%
“…68,208 Larger clinical trials are currently under way to examine whether similar models of care involving exercise and risk factor modification can be adapted and implemented among individuals with TIA or a broader range of clinical presentation after stroke. 209,210 These trials represent important steps toward the development of optimal secondary prevention strategies that integrate exercise interventions into a comprehensive risk-reduction program for stroke survivors.…”
Section: Exploring Effective Models Of Carementioning
confidence: 99%
“…Protocols for CCR after TIA/mild stroke have been published. 13,14 However, to our knowledge, there has been no previous prospective investigation of CCR early after TIA/MNDS. We hypothesized that an existing 6-month CCR program, in collaboration with a stroke prevention clinic (SPC), could provide feasible, effective secondary prevention following TIA/MNDS, without duplication of infrastructure and expertise.…”
mentioning
confidence: 99%